The role of SGLT2 inhibitors beyond glucose-lowering to cardio-renal protection - J. Karalliedde (Российский кардиологический журнал)
People with type 2 diabetes mellitus (T2DM) are at high risk of developing cardiovascular disease (CVD) and kidney disease. This enhanced cardio-renal risk persists despite improvements in care and treatments over the last 20 years. Intensive glucose control alone does not substantially reduce the risk of CVD and end stage kidney disease (ESKD). However, in 2015 the landmark EMPA-REG trial demonstrated for the first time the benefits of Empagliflozin a sodium-glucose co-transporter 2 (SGLT2) inhibitor on CVD events and mortality in people with T2DM. Since this trial several other SGLT2 Inhibitors including Dapagliflozin and Canagliflozin have demonstrated CVD benefits. SGLT2 inhibitors have also demonstrated significant reductions in the risk of hospitalization for heart failure (HHF) and ESKD. As a consequence of this growing evidence, there has been a shift in the focus of care in T2DM from glucose management to preservation of organ function. SGLT2 inhibitors have emerged as key treatment to reduce CVD, HHF and prevent progression of kidney disease. The benefits for reducing HHF and preventing ESKD have been observed in people with and without T2DM in large randomised controlled clinical trials. In T2DM the positive effects of SGLT2 inhibitors occur early and are independent of their glucose lowering effects. It is vital that all clinicians recognise the remarkable benefits of SGLT2 inhibitors and use this important class of drugs promptly and early to prevent CVD, HHF and ESKD.